MODEL INKLUSI DALAM PEMBELAJARAN PENDIDIKAN JASMANI (Studi Eksperimen di Sekolah Menengah Pertama Negeri 8 Tasikmalaya) - Cucu Hidayat (Fakultas Keguruan dan Ilmu Pendidikan Universitas Langlangbuana, 2008)
The purpose of the research is to find out the effects of teaching style and student attitude toward the physical education learning outcome. The research was conducted to the students at the eigth Secondary School Tasikmalaya, in period of 2007/2008 with samples 40 students of the seventh grade selected randomly.The result of the research conclusion that there are: (1) The students physical education learning outcome by using inclution teaching style is better than those by practice teaching style (2) The students who have positif attitude, and used inclution teaching style is better than those using practice teaching style of physical education learning outcome (3) The students who have negative attitude, and used practice teaching style is better than those using inclution teaching style of physical education laarning outcome (4) There is an interaction between teaching style and student attitude toward of students physical education learning outcome.So the students physical education learning outcome who have positif attitude can be improved by using inclution teaching style.Keywords: inclution teaching style, practice teaching style